A biobank for complex post-traumatic stress disorder (C-PTSD) and PTSD: study protocol for a cross-sectional study - Alice Mok; Chrystal Douflias; Lena K. L. Oestreich (European Journal of Psychotraumatology)
Background Complex Post-Traumatic Stress Disorder (C-PTSD) is a severe mental illness recently defined in the International Classification of Diseases 11th edition. In addition to the classic PTSD symptoms of avoidance, re-experiencing, and hypervigilance, it includes disturbances in emotion regulation, negative self-concept, and interpersonal relationships. Emerging evidence suggests C-PTSD has distinct neurobiological profiles compared to PTSD, but comprehensive investigations are lacking. This study aims to explore the neural mechanisms associated with C-PTSD, identifying distinct and shared brain alterations in C-PTSD and PTSD, while establishing a biobank incorporating neuroimaging, inflammatory, physiological, genetic, and psychosocial measures.Methods This cross-sectional study will compare three groups: individuals with C-PTSD (n = 40), PTSD (n = 30), and trauma-exposed healthy controls (n = 30). During a single visit, participants will undergo MRI scanning including structural, diffusion-weighted, resting-state, and task-based functional MRI. Blood samples will be collected for inflammatory marker analysis, and Genome-Wide Association Studies (GWAS). Participants will complete validated psychosocial self-report measures assessing trauma history, resilience, social support, emotion regulation, sleep quality, and mental health symptoms. Additionally, participants will wear an Actigraph smart watch for seven days to collect actigraphy-derived physiological data, including sleep patterns and heart rate variability. All de-identified data will be made openly available on the Open Science Framework upon publication of the main study findings, in accordance with ethical approvals and institutional guidelines for privacy and data security.Conclusion This comprehensive protocol addresses significant gaps in understanding C-PTSD through its multimodal approach. By comparing C-PTSD, PTSD, and trauma-exposed controls, the study aims to identify neurobiological markers specific to C-PTSD, potentially supporting its diagnostic distinction and informing targeted treatment approaches. Integrating neuroimaging, inflammatory, genetic, and psychophysiological measures acknowledges the complex interactions between biological systems in trauma responses. Findings may help inform future research on personalized intervention strategies by identifying potential biological profiles and resilience factors associated with trauma-related outcomes.